Evaluation of estrogenic effects of phthalate analogues using in vitro and in vivo screening assays - Kim, Youn-Jung; Ryu, Jae-Chun (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2006)
Phthalate analogues are a plasticizer and solvent used in industry. Phthalates were classified in the category of "suspected" endocrine disruptors. The purpose of our study was to screen and elucidate the endocrine disrupting activity of seven phthalate analogues. E-screen assay was performed in MCF-7 human breast cancer cells with seven phthalate analogues. In this cell proliferation assay, benzyl butyl phthalate (BBP) and dibutyl phthalate (DPB) showed high estrogenic activity. Their relative proliferation efficiencies (RPE) were 109 and 106%, respectively In vitro estrogen receptor (ER) binding assay, BBP di-n-octyl phthalate (DOP) and dinonyl phthalate (DNP) showed weak relative binding affinity (RBA: 0.02%) compared to 17 beta-estradiol (E2) (RBA: 100%). In uterotrophic assay, E2 produced a significant increase, whereas four tested phthalate analogues had potential estrogenic effects in vitro did not increased in uterus weight in immature rats. From these results, we demonstrated that phthalate analogues exhibit weak estrogenic activity in vitro assays at high concentrations. Although phthalates induced an increase in MCF-7 cell proliferation by an estrogenic effect, they could not induce a uterus weight increase in vivo. From these, we may suggest that these phthalate analogues are easily metabolized to inactive forms in vivo. Further investigation in other in vitro and in vivo experimental systems might be required.
Keywords: ENDOCRINE-DISRUPTING AGENTS; BUTYL BENZYL PHTHALATE; PSEUDOPREGNANT RATS; ESTERS; CHEMICALS; DI(2-ETHYLHEXYL)PHTHALATE; WILDLIFE; HUMANS; HEALTH; ACID